2021
DOI: 10.3390/bios11060191
|View full text |Cite
|
Sign up to set email alerts
|

Portable Chemiluminescence-Based Lateral Flow Assay Platform for the Detection of Cortisol in Human Serum

Abstract: In this study, we developed the portable chemiluminescence (CL)-based lateral flow assay (LFA) platform for the detection of cortisol in human serum. Cortisol is well-known as a stress hormone due to its high relevancy for human mental and physical health, such as hypertension or depression. To date, a number of optical devices have provided the sensitive determination of levels of analytes. However, this modality type still requires costly optical modules. The developed CL platform is simply composed of two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…To overcome the short lifetime of the excited state limitation of fluorescence (Berezin and Achilefu, 2010), a luminescence process, in which a photon may be released after any time, was developed (Gaft et al, 2015). Chemiluminescence-based biosensors are another type of optical sensing device (Aboul-Enein et al, 1999), which measure the rate of photon production and generate light through a chemical reaction (Kim et al, 2021). In this optical biosensor, the analyte interacts with the immobilized biomolecule, which is marked with chemiluminescence species.…”
Section: Optical (Fluorescence Chemiluminescence-based Biosensor and ...mentioning
confidence: 99%
“…To overcome the short lifetime of the excited state limitation of fluorescence (Berezin and Achilefu, 2010), a luminescence process, in which a photon may be released after any time, was developed (Gaft et al, 2015). Chemiluminescence-based biosensors are another type of optical sensing device (Aboul-Enein et al, 1999), which measure the rate of photon production and generate light through a chemical reaction (Kim et al, 2021). In this optical biosensor, the analyte interacts with the immobilized biomolecule, which is marked with chemiluminescence species.…”
Section: Optical (Fluorescence Chemiluminescence-based Biosensor and ...mentioning
confidence: 99%
“…In this work, the LFA membrane consisted of gold nanoparticles conjugated by antibodies against cortisol. Another study reported a LFA platform made of ligand-coated quantum beads and specific nanobodies for early-stage diagnosis of malaria and cardiovascular diseases [ 80 ]. Both examples included smartphone integration for data visualization and analysis.…”
Section: Smartphone-based Biosensing Technologiesmentioning
confidence: 99%
“… 227 , 228 A portable chemiluminescence-based lateral flow assay platform was synthesized by conjugating AuNPs with the anti-cortisol and anti-horseradish peroxidase antibodies, which can be used for serum cortisol detection. 229 Besides, Long et al employed a Cy5-labeled and streptavidin-coated QD probes to detect plasma renin activities, which are tightly associated with hypertension and congestive heart failure. 228 …”
Section: Nanoparticle-based Diagnostic Strategies For Vascular Aging-...mentioning
confidence: 99%